Genetic Drift, Not Life History or RNAi, Determine Long-Term Evolution of Transposable Elements. (26th August 2016) - Szitenberg, Amir; Cha, Soyeon; Opperman, Charles H.; Bird, David M.; Blaxter, Mark L.; Lunt, David H.
Abstract: Transposable elements (TEs) are a major source of genome variation across the branches of life. Although TEs may play an adaptive role in their host's genome, they are more often deleterious, and purifying selection is an important factor controlling their genomic loads. In contrast, life history, mating system, GC content, and RNAi pathways have been suggested to account for the disparity of TE loads in different species. Previous studies of fungal, plant, and animal genomes have reported conflicting results regarding the direction in which these genomic features drive TE evolution. Many of these studies have had limited power, however, because they studied taxonomically narrow systems, comparing only a limited number of phylogenetically independent contrasts, and did not address long-term effects on TE evolution. Here, we test the long-term determinants of TE evolution by comparing 42 nematode genomes spanning over 500 million years of diversification. This analysis includes numerous transitions between life history states, and RNAi pathways, and evaluates if these forces are sufficiently persistent to affect the long-term evolution of TE loads in eukaryotic genomes. Although we demonstrate statistical power to detect selection, we find no evidence that variation in these factors influence genomic TE loads across extended periods of time. In contrast, the effects of genetic drift appear to persist and control TE variation among species. We suggest that variation in the tested factors are largely inconsequential to the large differences in TE content observed between genomes, and only by these large-scale comparisons can we distinguish long-term and persistent effects from transient or random changes.